The Justification of 'Justice'. Legal Practitioners' Accounts of Negotiated Case Settlements in Magistrates' Courts - Mulcahy, Aogán (The British journal of criminology, 1994)
Plea negotiations are frequently criticized on the basis that they may arise from deception, coercion, and unethical practices. Nevertheless, they are highly valued by legal practitioners and widely used as a means of case disposition. While denying that negotiations are bargains' for defendants, and distancing themselves from any involvement in sentencing, legal practitioners justify their participation in this highly criticized activity in three major ways. First, they view negotiated settlements as more efficient and predictable than trials. Secondly, through the entry of appropriate' guilty pleas, negotiated settlements are thought to achieve substantive justice by linking the disposition with the facts' of a case. Finally, trials are viewed as unnecessary as defendants are largely perceived as morally culpable and substantively guilty. The paper considers the ideological nature of these justifications, as well as their implications for efforts to reform the criminal justice system